Correlated Skin Surface and Tumor Motion Modeling for Treatment Planning in Robotic Radiosurgery - Yu, Shumei; Hou, Pengcheng; Sun, Rongchuan; Kuang, Shaolong; Zhang, Fengfeng; Zhou, Mingchuan; Guo, Jing; Sun, Lining (Frontiers in Neurorobotics, 2020)
In robotic radiosurgery, motion tracking is crucial for accurate treatment planning of tumor inside thoracic or abdominal cavity. Currently, motion characterization for respiration tracking mainly focuses on markers which are placed on surface of human chest. Nevertheless, limited markers are not capable of expressing the comprehensive motion feature of human chest and abdomen. In this paper, we proposed a method of respiratory motion characterization based on the voxel modeling of thoracoabdominal torso. Point cloud data from depth cameras were used to achieve three-dimensional modeling of the chest and abdomen surface during respiration, and a dimensionality reduction algorithm was proposed to extract respiratory features from the established voxel model. Finally, experimental results including the accuracy of voxel model and correlation coefficient were compared to validate the feasibility of the proposed method, which provides enhanced accuracy of target motion correlation than traditional methods that utilized external markers.